EvoWallet / Muhammad Fais Md Taha ... [et al.] - Md Taha, Muhammad Fais; Mohd Kamal, Muhammad Khalili Aysraf; Yuspani, Muhd Fakrurrazi; Zamri, Muhammad Zuhaili; Shamsul Kamal, Muhammad Naim (2018)
Wallets are becoming more and more redundant lately as smartphones progressively replace cash and cards, but the EvoWallet is the latest attempt to keep the wallet relevant in the 21st century. Aside from acting as a power bank and smart tag holder, the ultra-smart wallet also incorporates some nifty security features in case when someone where struck by a pilfering pickpocket. Pairing a wallet with a smartphone, or adding GPS-tracking capacities, don't seem to be new innovations in the world of sensible wallets. EvoWallet incorporates both features into its design with wallet or phone signaling an alarm if he/ she forget one of the other. GPS tracking also lets users follow their wallet in real time if it gets snatched or lost. The most novel part of EvoWallet is the tiny camera built into it. If the wallet is stolen and enters "lost mode", the camera takes sneaky snaps of anyone who opens it. The pictures are immediately sent to paired smartphone, meaning ones can not only track where the wallet is in real time, but also watch the thief go through owner’s stuff. This is made possible by a SIM card embedded within the wallet. Rounding out the list of functions is a built-in power bank that can charge smartphone, either with a cable or wirelessly if the device has that capability.